2020
DOI: 10.1051/sicotj/2020035
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of HIV and hepatitis C increases complication rates after total joint arthroplasty

Abstract: Introduction: As advances in efficacy of human immunodeficiency virus (HIV) and hepatitis-C virus (HCV) anti-viral medications increase, patients are able to maintain higher quality of lives than ever before. While these patients live longer lives, the unique patient population of those co-infected with both HIV and HCV increases. As these older patients seek orthopaedic care, it is important to understand their unique outcome profile. The purpose of this study was to evaluate the complication rate after total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In HIV patients, comorbidities and HAART play a fundamental role in the evolution of joint pathology [ 2 ]. Besides, the associated fracture risk increases in patients with HIV and HCV coinfection in parallel to the risk of secondary infection, as seen in our patient [ 8 ].…”
Section: Discussionsupporting
confidence: 61%
“…In HIV patients, comorbidities and HAART play a fundamental role in the evolution of joint pathology [ 2 ]. Besides, the associated fracture risk increases in patients with HIV and HCV coinfection in parallel to the risk of secondary infection, as seen in our patient [ 8 ].…”
Section: Discussionsupporting
confidence: 61%
“…involving 50 patients reported an overall complication rate of 22% and an infection rate of 6% in HIV infected patients, with a conclusion that HAART therapy reduces overall infection rates in total joint (hip/knee) arthroplasty. On the other hand, a study involving 133 patients having total hip/knee arthroplasty by Fang et al 33 . showed that coinfection with HIV and HCV led to a 41% complication rate compared with isolated HIV (7%) or HCV (12.5%) infection.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Jacob et al 32 involving 50 patients reported an overall complication rate of 22% and an infection rate of 6% in HIV infected patients, with a conclusion that HAART therapy reduces overall infection rates in total joint (hip/knee) arthroplasty. On the other hand, a study involving 133 patients having total hip/knee arthroplasty by Fang et al 33 showed that coinfection with HIV and HCV led to a 41% complication rate compared with isolated HIV (7%) or HCV (12.5%) infection. Theoretically, this may also apply to TER, and it is therefore important for patients undergoing elective TER to have HAART treatment and suppressed HIV viral loads with CD4 count optimization preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with HIV and HCV has been shown to be associated with increased postoperative complications including PJI, with HCV driving the risk [ [31] , [32] , [33] ]. We did not appreciate in our study population any significant difference in HIV rates in patients with PVL and UVL, while HIV coinfection was not a risk factor for PJI.…”
Section: Discussionmentioning
confidence: 99%